QIRÂ'AH SÎMIYÂIYAH FÎ AL-QISHSHAH AL-QUR'ÂNIYAH "ASHHÂB AL-SABT" - Souad Chabi (Arabi : Journal of Arabic Studies, 2017)
The semantic approach is one of the contemporary cretic approaches It reads text In second reading; By analyzing its meaning; Focus on both linguistic and non-linguistic signs; Such as space, time, human or animal characters, scenes and other elements of a text. So we tried to apply this reading on the story of the Quranic its story of the owners of the Saturday, and chose the title of our research, "read semiotics in the story of the owners of the Saturday". The purpose of this study is to examine and understand the verses of the Holy Quran on the one hand and to apply the Semantic approach on the other. We have followed the analytical descriptive approach appropriate to the nature of the subject. The most important results obtained through research are: The harmony of the scene in the story with the events, in each scene events marked a scene from another. The basis of decorating the event is associated with the characters. Quranic story is a reminder to people and a lesson.